2021
DOI: 10.1186/s12904-021-00845-9
|View full text |Cite
|
Sign up to set email alerts
|

Managing clinical uncertainty in older people towards the end of life: a systematic review of person-centred tools

Abstract: Background Older people with multi-morbidities commonly experience an uncertain illness trajectory. Clinical uncertainty is challenging to manage, with risk of poor outcomes. Person-centred care is essential to align care and treatment with patient priorities and wishes. Use of evidence-based tools may support person-centred management of clinical uncertainty. We aimed to develop a logic model of person-centred evidence-based tools to manage clinical uncertainty in older people. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 83 publications
(431 reference statements)
0
10
0
Order By: Relevance
“…A systematic mixed-methods review of studies evaluating person-centred tools around clinical uncertainty for a similar population highlights the benefits of tools measuring across need domains. 55 Tools targeting ‘comprehensive assessment and continuity of care’ were found to improve ‘outcomes of quality of death and dying, clinician’s global assessment, goal attainment and symptom burden’. 55 Any tools developed for older people with multimorbidity near the end of life must cover multiple, complex palliative care needs across domains of need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic mixed-methods review of studies evaluating person-centred tools around clinical uncertainty for a similar population highlights the benefits of tools measuring across need domains. 55 Tools targeting ‘comprehensive assessment and continuity of care’ were found to improve ‘outcomes of quality of death and dying, clinician’s global assessment, goal attainment and symptom burden’. 55 Any tools developed for older people with multimorbidity near the end of life must cover multiple, complex palliative care needs across domains of need.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Tools targeting ‘comprehensive assessment and continuity of care’ were found to improve ‘outcomes of quality of death and dying, clinician’s global assessment, goal attainment and symptom burden’. 55 Any tools developed for older people with multimorbidity near the end of life must cover multiple, complex palliative care needs across domains of need. Further, tools must also measure what matters most to the patients with which they are being used to have validity.…”
Section: Discussionmentioning
confidence: 99%
“…Models of uncertainty and evidence gaps from relevant literature reviews were outlined. [11,32,34,43,44] We then held focus groups with participants to explore their views on uncertainty and identify key areas for future research. This approach mirrored the idea generation stage of the nominal group technique and the first round of a Delphi process.…”
Section: Workhop Processmentioning
confidence: 99%
“…Discussion of main findings Communicating uncertainty was the top priority for participants, reflecting key evidence gaps and recommendations in this field. [32,47] In their narrative review of uncertainty communication, Simpkin et al identified a number of evidence gaps, including identifying individuals' communication preferences and tailoring communication to those preferences. [34] The question of how to maintain hope whilst communicating uncertainty was noted as a priority; this has been explored in cancer care, [48] but remains a key question in other serious illnesses.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation